If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + (4 + y) = 14 Remove parenthesis around (4 + y) 2 + 4 + y = 14 Combine like terms: 2 + 4 = 6 6 + y = 14 Solving 6 + y = 14 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + y = 14 + -6 Combine like terms: 6 + -6 = 0 0 + y = 14 + -6 y = 14 + -6 Combine like terms: 14 + -6 = 8 y = 8 Simplifying y = 8
| 395=(x-20) | | 5h+j+kl=2.6 | | 2(4+y)=14 | | 2(y+5)-4=14 | | 395=4x(x-20) | | S/2=3 | | 2+19x+cx= | | S*2=3 | | 9(f+3)=7(f+5) | | 2(y+6)-3=19 | | sqrt(528)= | | 24x+6x-8x+5x-36x=3-24-24+18 | | x-0.25x=1 | | 6(x-2)=3(x+8) | | Y1/2x-2 | | 0.1(n+76)=0.5n | | 6(3x+1)-14(2-4x)=3(-5x-4)+49x | | 1+(2+y)=10 | | x^2-7p-120=0 | | N+76=n | | (2x-1)2=7 | | 6.9x-2.6=18.1 | | 6x(2-x)=52 | | 25+4x=6x+9 | | 3(4x-1)-5(x+7)=3(x+1) | | x-1/5=x/2 | | 9/x=2/7 | | 4x+6*2-6=12x | | 9x-5=12y | | 5(6z-1)-5(z+1)=23(z+1) | | 4^3x-1=1/64 | | y^2+18y+45= |